Implementation of the parent involvement program at TKN Satap Tembong 01: strategies and benefits - Adawiah, Aulia Robiah; Safira, Azumah Lola; Lisdania, Elok; Madiyana; Shafira, Nadia; Rahima, Qhaysah Fara; Natalia, Wahyuli Setia; Raisa, Zahra Ulum (International Conference on Education in Primary and Early Childhood, Marine, Computer Information, and Logistics, 2025)
This study aims to explore the implementation of the parent involvement program at TKN Satap Tembong 01, focusing on the strategies used and the benefits obtained. Parental involvement is considered one of the important factors in supporting children's development, both academically and emotionally. This study uses a qualitative approach with observation, interview, and document analysis methods to obtain comprehensive data. The results of the study show that the parent involvement program at TKN Satap Tembong 01 is implemented through various strategies, such as regular communication, parenting activities, and collaboration in learning activities. The benefits of this program include improving the relationship between school and family, increasing children's motivation to learn, and creating a more supportive learning environment. This research makes an important contribution in understanding how parental involvement can be effectively implemented at the early childhood education level.
Keywords: parental involvement; implementation strategies; program benefits; qualitative methods; observation